2023
DOI: 10.1007/s40279-022-01805-w
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Factors Determining Critical Power

Abstract: The physiological determinants of high-intensity exercise tolerance are important for both elite human performance and morbidity, mortality and disease in clinical settings. The asymptote of the hyperbolic relation between external power and time to task failure, critical power, represents the threshold intensity above which systemic and intramuscular metabolic homeostasis can no longer be maintained. After ~ 60 years of research into the phenomenon of critical power, a clear understanding of its physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 179 publications
2
8
1
Order By: Relevance
“…For instance, Ansdell et al (2019) showed female knee-extensors had a greater relative critical torque than males during single-limb exercise. Whereas during cycling, where O 2 delivery is a determinant of critical power (Goulding & Marwood, 2023), this metabolic threshold was not different between sexes (Ansdell et al, 2020a). Whilst consensus on whether O 2 delivery does (Hughson et al, 2001) or does not (Grassi, 2001) limit τV O 2 has not been reached, it is conceivable that during tasks where O 2 delivery and utilisation are both determinants in the metabolic response to exercise, the superior female skeletal muscle oxidative capacity (Cardinale et al, 2018) and vasodilatory response to exercise (Parker et al, 2007) is counteracted by an inferior O 2 carrying capacity (Murphy, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Ansdell et al (2019) showed female knee-extensors had a greater relative critical torque than males during single-limb exercise. Whereas during cycling, where O 2 delivery is a determinant of critical power (Goulding & Marwood, 2023), this metabolic threshold was not different between sexes (Ansdell et al, 2020a). Whilst consensus on whether O 2 delivery does (Hughson et al, 2001) or does not (Grassi, 2001) limit τV O 2 has not been reached, it is conceivable that during tasks where O 2 delivery and utilisation are both determinants in the metabolic response to exercise, the superior female skeletal muscle oxidative capacity (Cardinale et al, 2018) and vasodilatory response to exercise (Parker et al, 2007) is counteracted by an inferior O 2 carrying capacity (Murphy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite more aerobically-suited skeletal muscle, females have lower levels of haemoglobin (Murphy, 2014), which is thought to impair O 2 carrying capacity during exercise (Harms et al ., 1998; Diaz-Canestro et al ., 2022). During exercise where O 2 delivery and utilisation are both limiting factors (e.g., cycling, Goulding & Marwood, 2023), these factors are thought to counteract each other to enable comparable relative metabolic thresholds (i.e., critical power) between the sexes (Ansdell et al ., 2020b). To date, the only investigation to systematically investigate the oxidative adjustment at the onset of exercise between sexes did so during low intensity treadmill walking (Beltrame et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…severe exercise), a steady‐state is unattainable for both trueV̇O2${\dot{V}}_{{{\mathrm{O}}}_{\mathrm{2}}}$ and blood [lactate], with trueV̇normalO2max${\dot{V}}_{{{\mathrm{O}}}_{\mathrm{2}}{\mathrm{max}}}$ being attained shortly prior to task failure (Goulding & Marwood, 2023; Goulding et al., 2021; Jones et al., 2011; Poole et al., 2016). In practical terms, healthy individuals perform most activities of daily living below GET, whereas for those with chronic diseases, the elderly and very inactive individuals, activities of daily living may be carried out above GET and/or critical power (Goulding & Marwood, 2023; Poole et al., 2021). These thresholds therefore partition the full range of aerobic activities performed in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological mechanisms that underpin the possible improvements in exercise performance seen as a result of IPC, have not been fully elucidated [9]. A number of mechanisms have however been postulated for any positive effects of IPC, including augmented oxygen uptake kinetics [10], which are an important determinant of aerobic exercise performance [11,12]. It is proposed that increases in blood flow through an upregulation of endothelial function following IPC allows for an improved (reduced) time constant () of the fundamental phase of oxygen uptake kinetics, in addition to an attenuation of the slow component [1].…”
Section: Introductionmentioning
confidence: 99%